Implementation Of The Internal Control System For Cash Disbursements At Nahdlatul Ulama Hospital Jombang - Oktaviani, Yully; Purbowati, Rachyu; Nurhayati, Nurhayati (STIE PGRI Dewantara Jombang, 2019)
This study aims to determine the application of the Internal Control System for Cash Expenditures at the Nahdlatul Ulama Hospital Jombang. The type of research was descriptive qualitative. The data used were primary data obtained through in-depth interviews with key informants at RSNU. The results showed that the hospital had implemented the elements of internal control properly because it was in accordance with the objectives of the agency, namely maintaining the company's assets, checking the accuracy and reliability of accounting data. However, there were still a number of procedures that were still inadequate and evaluation was still needed, among others, the internal control system still had a dual function, had never been checked suddenly, and periodic physical cash matching had not been regularly scheduled.